Implementasi pengelolaan digital institutional repository pada perpustakaan PTKIN dan dampaknya pada terhadap pemeringkatan di webometrics - Sri Rohyanti Zulaikha; Ari Sholihin; Marwiyah Marwiyah; Labibah Labibah (Al Maktabah, 2017)
An institution which creates and organizes accessible information resources both local and remote based on information technology, remains to be one of interesting topics discussed by academicians and practitioners in Library and Information nowadays. This digitized infor-mation which is called as ‘institutional repository’ relates to one of researches in digital library management. This repository is developed not only to provide access easily and globally or to create digital archieve as long-term stable resources to ensure their quality and survivability, but it is also addressed to institutional prestige and excellence. Therefore, it is more often viewed as institutional ranking both national and international that we call as the webometrics repository. However, librarians have challenge and opportunity to compete for the best insti-tution in organizing the repository. The competition has been lasting among PTKIN’s libraries (libraries in State Islamic University) which participate and devote highly attention to organize and develop their repositories. In this case, how do the PTKIN libraries organize their reposi-tories and to what extent the organizing has impact on ranking webometics of repository? This paper is trying to elaborate addressed to the questions by doing research into six PTKIN’s libraries using quantitative method. Indicators to evaluate in organizing the repository use the same indicators as webometrics’ standards. They are size, visibility, rich files, and scholar. The findings show that organizing the repository has been conducted by three PTKIN’s libraries (UIN Yogyakarta, UIN Jakarta, and UIN Riau) which reached the higher score from 1 to 3 respectively. These results are in line with place of three institutions in ranking webometrics. Meanwhile, another three PTKIN’s libraries (UIN Malang, UIN Bandung, dan UIN Makasar) have very different score with the aforementioned three PTKIN’s libraries. The repository of last three PTKIN’s libraries shows that there is no one of them registered in the ranking webo-metrics. In conclusion, organizing of the repository in six PTKIN’s libraries has relevant impact on the ranking webometrics.